1986
DOI: 10.1177/34.6.3009604
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of two angiotensin I-converting isoenzymes in the reproductive tract of the male rabbit.

Abstract: The male reproductive tract contains two different isoenzymes of angiotensin I-converting enzyme (ACE), i.e., pulmonary and testicular ACE. The present study shows selectively the cellular distribution ofthe ACE isoenzymes in the reproductive tract of male rabbit, using indirect immunofluorescence or immunoperoxidase methods. Testicular ACE was found in the seminiferous tubules of the testes in spermatocytes containing mature spermatids, and in spermatids within the epididymal tubular lumen in sexually mature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 10 publications
5
32
1
Order By: Relevance
“…Some authors (14,15) found angiotensinconverting activity in normal, 24-hour urines; possibly they were measuring the physiological replacement of the renal tubular brush-border whose epithelial cells are sedimentable. In view of the high specific angiotensin-converting activities in the male genital tract (16,17), a gonadic or prostatic origin of urinary angiotensin-converting enzyme might have been expected, but we found no difference between males and females; in particular, normal men did not excrete angiotensin-converting activity in the urine. The absence of a correlation between this urinary enzymatic activity and proteinuria, and even more the lack of dependence of this activity on the indices of glomerular function, such as creatininuria or albuminuria, eliminate the possibility of a passage of the plasmatic enzyme throughout the glomerular filter.…”
Section: Discussioncontrasting
confidence: 40%
“…Some authors (14,15) found angiotensinconverting activity in normal, 24-hour urines; possibly they were measuring the physiological replacement of the renal tubular brush-border whose epithelial cells are sedimentable. In view of the high specific angiotensin-converting activities in the male genital tract (16,17), a gonadic or prostatic origin of urinary angiotensin-converting enzyme might have been expected, but we found no difference between males and females; in particular, normal men did not excrete angiotensin-converting activity in the urine. The absence of a correlation between this urinary enzymatic activity and proteinuria, and even more the lack of dependence of this activity on the indices of glomerular function, such as creatininuria or albuminuria, eliminate the possibility of a passage of the plasmatic enzyme throughout the glomerular filter.…”
Section: Discussioncontrasting
confidence: 40%
“…Further, different mRNAs encoded the two isozymes, and they were regulated differently by hormones (El-Dorry et al, 1982b). Using immunologic approaches, testis ACE was identified in male germ cells, whereas somatic ACE was found in the epididymal epithelium, cells of the vas deferens, and within seminal fluid (Berg et al, 1986;Brentjens et al, 1986;Danilov et al, 1987).…”
Section: E Role Of Testis Angiotensin-converting Enzymementioning
confidence: 99%
“…Interestingly, both renin and angiotensinogen mRNA are present and localized to the testicular Leydig cells of mouse testes (Pandey et al 1984a, Deschepper et al 1986, Dzau et al 1987. These data suggest that a locally , Pandey et al 1984b, Berg et al 1986, Wong & Uchendu 1991, Mukhopadyay et al 1995, Williams et al 1995*, Kohn et al 1998a, Pinterova et al 2000*, Nassis et al 2001 Angiotensin II Testis; epididymis; prostate; seminal plasma Okuyama et al 1988, Zhao et al 1996, O'Mahony et al 2000, Dinh et al 2001b Angiotensins III, IV or (1-7)…”
Section: Components Of the Ras In The Male Reproductive Systemmentioning
confidence: 99%
“…Moreover, ACET is found exclusively in late pachytene spermatocytes and mature spermatozoa (Berg et al 1986, Sibony et al 1993 while the somatic form of ACE (sACE) is found in the Leydig cells, epididymis and prostate (Nassis et al 2001).…”
Section: Components Of the Ras In The Male Reproductive Systemmentioning
confidence: 99%